Complete Genome Sequence of the Genotype 4 Hepatitis E Virus Strain Prevalent in Swine in Jiangsu Province, China, Reveals a Close Relationship with That from the Human Population in This Area - Wang, Hua (American Society for Microbiology, 2012)
Hepatitis E virus (HEV) is a zoonotic pathogen of which several species of animal were reported as reservoirs. Swine stands out as the major reservoir for HEV infection in humans, as suggested by the close genetic relationship of swine and human viruses. In a previous study, we sequenced the complete genome of a human genotype 4 HEV strain (HM439284) that is prevalent in Jiangsu Province, China. Here we report the complete genome of one genotype 4 HEV strain which is prevalent in swine herds in Jiangsu Province. Phylogenetic analysis indicated that the swine HEV strain in the present study has high sequence homology (>92%) with the genotype 4 HEV strains prevalent in the human population of Jiangsu Province. These results suggested that the genotype 4 HEV strain in the present study is involved in cross-species transmission between swine and humans in this area.